The Effectiveness of Reducing Hardness in the Filtration Process Using Mixed Media with Detention Time Variations - Ferry WF Waangsir; I Gede Putu Arnawa; Johanis JP Sadukh; Edwin M. Mauguru (Postgraduate, University of Mataram, 2023)
The problem that is often faced in groundwater management, especially deep groundwater such as boreholes is hardness. This can happen because in the process of taking it from the soil through various layers of soil including limestone soil containing Ca and Mg, so that the water becomes hard. Hard water is found in areas where the top soil layer is thick and there is limestone formation. This study aims to identify the physical quality and hardness level of clean water sourced from dug wells and drilled wells, after treatment through filtration methods. Filtration is carried out using mixed media with variations in residence time in the filtration media, namely 30 minutes, 60 minutes and 90 minutes. The results showed that the effectiveness of reducing hardness in dug wells and drilled wells was highest for a variation in 90 minutes, For dug wells, the effectiveness of 90 minutes of residence time reached 9.18% and for drilled wells, the effectiveness reached 16.36%.